2017
DOI: 10.1111/1752-1688.12508
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Subsidies from Hillslope Alder Stands to Streamside Wetlands and Headwater Streams, Kenai Peninsula, Alaska

Abstract: We examined nitrogen transport and wetland primary production along hydrologic flow paths that link nitrogen‐fixing alder (Alnus spp.) stands to downslope wetlands and streams in the Kenai Lowlands, Alaska. We expected that nitrate concentrations in surface water and groundwater would be higher on flow paths below alder. We further expected that nitrate concentrations would be higher in surface water and groundwater at the base of short flow paths with alder and that streamside wetlands at the base of alder‐ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Shaftel et al (2012) observed a similar pattern in some of the same streams, where some mid-level-alder sites had lower than expected DIN concentrations in July and September than in May. We suspect that increased temperature-driven uptake or summer low flows (i.e., reduced hydrologic connection) along soil flow paths decreased the amount of alder-derived N being exported to the streams (Callahan et al 2017). Thus, N 2 fixation rates in these streams could be sensitive to temperature or precipitation changes at the reach and catchment scales via controls on landscape DIN export.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Shaftel et al (2012) observed a similar pattern in some of the same streams, where some mid-level-alder sites had lower than expected DIN concentrations in July and September than in May. We suspect that increased temperature-driven uptake or summer low flows (i.e., reduced hydrologic connection) along soil flow paths decreased the amount of alder-derived N being exported to the streams (Callahan et al 2017). Thus, N 2 fixation rates in these streams could be sensitive to temperature or precipitation changes at the reach and catchment scales via controls on landscape DIN export.…”
Section: Discussionmentioning
confidence: 54%
“…Because alder is an obligate N 2 fixer, landscape cover and distance from streams (length of soil flow path) determine N delivery from alder to streams (Shaftel et al 2012, Callahan et al 2017. Alder presence can be a robust predictor of N availability in areas with minimal anthropogenic N sources.…”
Section: Discussionmentioning
confidence: 99%
“…Second, plant species composition in the sub‐basin may influence nitrogen levels in streams. Specifically, alders are nitrogen‐fixing shrubs responsible for increasing stream nitrate via groundwater (Callahan et al ). Thus, the high levels of alders observed at moose impacted sites could further increase nitrogen subsidies in these streams and may explain some of the variation in total nitrogen in the study sites (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Streams with higher discharges are expected to have lower electrical conductivity and total nitrogen due to dilution. Streams surrounded by more speckled alders, a riparian nitrogen‐fixing shrub, are expected to have higher levels of total nitrogen (Callahan et al ).…”
Section: Methodsmentioning
confidence: 99%
“…We conducted our experiment in 2013 on the western Kenai Peninsula of Alaska in a first‐order tributary of the South Fork Anchor River, previously identified as SANC 1203 (King, Walker, Whigham, Baird, & Back, ; Shaftel, King, & Back, ; Walker, King, Whigham, & Baird, ; 59.77974°N, 151.55518°W; Figure a,b). We selected SANC 1203 for this experiment for several reasons: (1) well‐characterised catchment and water chemistry from previous studies, including cover estimates of wetlands (32%, largely discharge slope and riparian wetlands that export limited quantities of DOC; Shaftel et al, ; Walker et al, ; Whigham, Walker, King, & Baird, ) and N 2 ‐fixing alder (12.6%; Shaftel, King, & Back, ; Shaftel et al, ); (2) relatively high nutrient availability, specifically PO 4 ‐P ( c. 20–50 µg/L) related to volcanic deposition in the region and NO 3 ‐ N ( c. 200–500 µg/L) directly related to the alder (Callahan et al, ; Shaftel et al, ); (3) relatively low levels of ambient DOC (1.8–3.3 mg/L at baseflow) when compared to peat‐rich catchments nearby (10–20 mg/L, Walker et al, ); (4) similar channel width (1.4 m), depth (0.12 m), substrate (gravel‐cobble, woody debris), riparian vegetation (bluejoint grass: Calamagrostis canadensis ), and gradient (5%) over a distance of sufficient length to delineate reaches that would be comparable prior to any experimental manipulation; (5) representative of headwater streams throughout the Kenai lowlands (Whigham et al, ) and other boreal regions; and (6) moderate to high densities of juvenile Dolly Varden ( Salvelinus malma , Figure c), the most widespread and abundant salmonid in headwater streams in this region (King et al, ).…”
Section: Methodsmentioning
confidence: 99%